Relasi Sains Dan Agama dalam Perpspektif Ian Graeme Barbour - Hidayah, Husnul; Iriyadi, Deni; Gufron, Iffan Ahmad (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2022)
Science and religion are inseparable sciences on the grounds that they are closely related, with the proposition that all knowledge cannot be separated from the sources of Islamic law, especially the Qur'an and Hadith. However, some scientists argue that science and religion are two different things. This study aims to provide an overview of Ian G Barbour's views on science and religion. This research has an object of study related to the relationship between religion and science, especially those related to various forms of the relationship between the two, both obtained from scientific studies. This research is library research that uses content analysis to examine various information about the things being studied. The results of the study show that science is considered something clear where the truth can be proven by reason, while religion is considered something theoretical. One of the researchers who emphasize the relationship between science and religion is Ian G. Barbour. In this conversation, Barbour observes that the relationship between science and religion is separated into four methodologies: struggle, autonomy, discourse, and combination. science and religion are types of knowledge that people have: common sense, myths, belief systems, and works. From one point of view, the unequivocal value of truth turns out to be definite and immediate, and eternal in view of the fact that it comes from something that is certain and never dies, namely the creator or god.